THE EFFECT OF JOB CONDITION, INTERPERSONAL COMMUNICATION, AND PERCEIVED ORGANIZATIONAL SUPPORT ON EMPLOYEE PERFORMANCE OF PDAM COMPANY SURABAYA, INDONESIA - Purwanti Purwanti (JMM17 : Jurnal Ilmu ekonomi dan manajemen, 2020)
The aims of this study is to examine the effect of working condition, Interpersonal Communication and Perceived Organizational Support on performance employment of PDAM  company, Surabaya, Indonesia. Methode used in this research is descriptive Explanatory which is a method that explains causal relationships between the variables observed. This research is limited by data collected from a sample of the population to represent the whole population. Data analyzed by multiple linear regression to, T-test, and F test, with SPSS program. The test result of multiple regression show that every increasing Working condition, Interpersonal Communicationa and perceived organizational support will increase performance of the employes. The results of Hyphothesis thest shows that as a simultaniously there were significant effect between Working condition, Interpersonal Communicationa and perceived organizational support to employee performance, eventhough as a partially that Working condition, and Interpersonal Communicationa are significant effect to employee performance but Perceived Organizational Support has no significant effect to employee performance.